Epidemiological Factors Affecting Mental Health Among Medical Faculty Students at Elmergib University, Libya - Mohamed Sryh (African Journal of Advanced Pure and Applied Sciences, 2025)
Medical education and training can directly contribute to the development of mental disorders among students. This study aims to assess the prevalence of mental disorders among medical faculty students at Elmergib university and assess the effect of different epidemiological factors on students’ mental health status. A descriptive study targeted 377 students at medical faculty at Elmergib university Alkhoms city Libya, participants were selected randomly for the study, through online questionnaire demographic, socio-economic, academic, health related factors were assessed. DASS 42 scale (Arabic version) was used to assess mental disorders among participants. Among 377 participants 275 were female (72.9%), and 40 of them had low academic grade (10.6%), 338 of them were non married (89.7%), 292 had low income (77.5%), 71 of them had family history of mental disorders (18.8%). Our study found that 1 in every 2 participant students have some degree of mental disorder, and 1in every 4 participants have severe form of mental disorder. Mental disorders were found to be significantly associated with low academic grade (OR=2.05), Non married marital status (OR=2.63) and family history of mental disorders (OR=2.25). Medical education is directly contributing to the development of mental disorders because of the high scholastic workload, stressful clinical training programs and financial burdens. Female students with low academic grades, non married, with low income and positive family history of mental disorders should receive immediate mental health assessment and support.